Pengaruh Self Assessment System, Penagihan Pajak Dan Pemeriksaan Pajak Terhadap Penerimaan Pajak Penghasilan - Sintiawati Sintiawati; Susan Grace V Nainggolan; Rahmad Dianta Purba (Jurnal Minfo Polgan, 2026)
The purpose of this study is to examine whether the self-assessment system, tax collection, and tax audits have a significant effect on income tax revenue at the Medan Polonia Tax Office (KPP Pratama). This study uses a quantitative approach with primary data obtained through distributing questionnaires to taxpayers directly and online via Google Form. The sample size is 400 taxpayers with a 5% error rate. The sampling technique uses nonprobability sampling using accidental sampling. Data were analyzed using multiple regression analysis methods which produce the equation Income Tax Revenue = 14.898 + 0.128 Self Assessment System + 0.180 Tax Collection + 0.111 Tax Audit + e. The researcher also used a 5% significance level. The results of the study partially indicate that the Self Assessment System has a significant effect on Income Tax Revenue, Tax Collection partially has a significant effect on Income Tax Revenue, and Tax Audit is partially not significantly affected by Income Tax Revenue. The results of the study simultaneously indicate that the Self Assessment System, Tax Collection, and Tax Audit simultaneously have a significant effect on Income Tax Revenue. The coefficient of determination is 0.072, meaning that 0.72% of the Income Tax Revenue variable can only be explained by the Self Assessment System, Tax Collection and Tax Audit variables, and the remaining 99.28% of the Income Tax Revenue variable is explained by other variables not included in this study.